1996
DOI: 10.1007/bf02355066
|View full text |Cite
|
Sign up to set email alerts
|

Ileocolic intussusception in adult due to malignant lymphoma in the cecum with intramural metatasis

Abstract: A rare adult case of intussusception caused by malignant lymphoma of the cecum with intramural metastasis is reported. The patient was a 24-year-old man. Ileocolic intussusception was diagnosed by characteristic findings on abdominal computed tomography. Endoscopic examination revealed a massive protuberant tumor, 3 cm in diameter, and a semipedunculated polyp, 1 cm in diameter, in the cecum, which had caused the ileocolic intussusception. Endoscopic biopsy specimens failed to yield a definitive diagnosis hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A search of PubMed from 1990 to 2017 found only one case of DIS of colonic malignant lymphoma with intussusceptions (12). Thus, the present case is the first report of DIS of colonic epithelial neoplasm.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…A search of PubMed from 1990 to 2017 found only one case of DIS of colonic malignant lymphoma with intussusceptions (12). Thus, the present case is the first report of DIS of colonic epithelial neoplasm.…”
Section: Discussionmentioning
confidence: 63%
“…DIS is a type of cancerous metastasis that is regarded not only as a marker to identify the surgical margin during operation (1) but also as an index for the prognosis of rectal cancer (12). It has also been reported to be related to the depth of cancer invasion (5).…”
Section: Discussionmentioning
confidence: 99%
“…In our case, a 53-year-old male with diffuse large B-cell lymphoma involving the terminal ileum and had caused an ileocolic intussusception. Our literature search revealed that few cases of B-cell lymphoma, presenting as intussusceptions of terminal ileum, in HIV-seronegative adults, have ever been reported [58]. …”
Section: Discussionmentioning
confidence: 99%